Creative negotiations. Romania–America 1920–1940 - MIHALY, Roxana; ANDRAȘ, Sonia D. (2024)
Throughout the interwar period, America’s interest in Romania grew andencompassed not only political, diplomatic, and historical aspects but alsofinancial, cultural, and educational contributions. Thus, the Romanian-American ties throughout the interwar period suggest innate complexityand dynamism. This volume presents novel techniques and issues examinedfrom an interdisciplinary, multi-perspective, and intercultural outlook. Theseapproaches are derived from ideas such as discussion, negotiation, educational,and cultural communications.